Indoor carpet skiing in the rehabilitation of competitive alpine skiers following ACL reconstruction: Is it an option? - Spörri, J.; Kröll, J.; Fasel, B.; Aminian, K.; Müller, E. (Science and Skiing VII, 2018)
Alpine ski racing is a competitive sport that puts athletes at high risk for suffering traumatic injuries (Bere, Florenes, Nordsletten, & Bahr, 2013; Florenes, Bere, Nordsletten, Heir, & Bahr, 2009; Florenes, Nordsletten, Heir, & Bahr, 2012; Hildebrandt & Raschner, 2013; Pujol, Blanchi, & Chambat, 2007; Stenroos & Handolin, 2014; Westin, Alricsson, & Werner, 2012). The most common injury location (expressed as a body part) has been reported to be the knee (35.6%), with a rupture of the anterior cruciate ligament (ACL) being the most frequent specific type of injury (13.6% of all recorded injuries) (Florenes et al., 2009; Florenes et al., 2012). As in every competitive sport, quickly and safely returning to sport is a priority; therefore, timely surgeries and effective rehabilitation programs are important for athletes recovering from injury. Typically, the rehabilitation of a competitive alpine skier following ACL reconstruction takes 16-24 weeks and follows a predefined sequence of four phases (Kokmeyer, Wahoff, & Mymern, 2012)